The impacts of audit committee expertise on real earnings management: Evidence from Hong Kong - Kwok Yip Cheung; Chi Veng Chung (Cogent Business & Management, 2022)
This study examines the impacts of seven types of audit committee expertise (accounting academic, auditing, finance academic, CEO or finance director, other finance, industry and legal expertise) on real earnings management. 1054 firm-year observations are used in the study. The sample firms are collected from Hong Kong Hang Seng Composite Index between 2010 and 2015. Real earnings management are measured as abnormal cash flows, abnormal production costs, and abnormal discretionary expenditures. Using dynamic panel difference GMM model that is robust for endogeneity caused by reverse causality, we find that Hong Kong firms having strong audit committee expertise are more likely to have higher levels of real earnings management. Overall, our findings support the view that the strong accounting, finance and legal experts on the audit committee, no matter whether they have practical experience or academic experience, encourage managers to switch their earnings management strategies whilst CFO or finance director expertise constrains real earnings management. The findings are of potential interest to policymakers, professionals, boards of directors, audit firms and academics.
Keywords: 650; agency theory; audit committees; discretionary accruals; Hong Kong; oversight effectiveness